Prevalence of Different Gastrointestinal Manifestations in Patients with Covid 19 Presenting to Gastroenterology OPD at Rawal Institute of Health Sciences, Islamabad - Anwar Hussain Abbasi, Aasia Zameer, Anum Umar, Hina Andaleeb, Khawaja Ashfaq Ahmed, Nadeem Yousuf (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: The objective behind this study was to determine the prevalence of different gastrointestinal manifestations in patients with COVID-19 presenting to gastroenterology OPD at Rawal Institute of health sciences, Islamabad Methods: this was a descriptive observational hospital-based study conducted through a convenient sampling technique. All the adult males and females diagnosed as COVID-19 for the first time were included in this study. Pregnant females, concomitant viral hepatitis, typhoid fever, known gastrointestinal disease, and those who did not consent to participate were excluded from this study. Proforma was used to collect the relevant data. Data regarding GI symptoms were collected and presented in the form of frequency and percentages. Results: Final analysis was performed on 193 COVID-19 positive patients. Diagnosed patients were mostly young with mean age was 39.42±18.29 years. More than 68% of the patients were males. Sixty-eight (35.23%) of the COVID-19 PCR positive patients presented with symptoms of gastrointestinal manifestations and the most common GI symptom was presence of Dysgeusia (52.94%, n = 36). Conclusions: Most of our study subjects belongs to young age group. The prevalence of GI manifestations are quite high as observed in our study and the most common GI symptoms was dysgeusia. Keywords: COVID-19 infection, gastrointestinal symptoms, clinical manifestation, Pakistan